The Effect of Using Information Technology on Employee Performance Through Employee Motivation at the Surabaya City Library and Archives Service - Pudji Astuti; Andre Dwijanto Witjaksono; Anang Kistyanto (Universitas Pendidikan Indonesia, 2025)
The aims of this study to analyze the influence of 91) the use of information technology on work motivation, (2) the use of information technology on employee performance, (3) employee work motivation on employee performance, and (4) the use of information technology on employee performance mediated by motivation work of employees of the Surabaya City Library and Archives Service. This research is explanatory research. The population used in this research were employees of the Surabaya City Library and Archives Service as a sample of 195 employees. The research was carried out by providing a questionnaire that represented the research variables. Data obtained was analyzed using the SEM (Structural Equation Model) method in AMOS 21 software. The results obtained from this research are (1) there is an influence of the use of information technology on work motivation, (2) there is an influence of the use of information technology in employee performance, (3) there is an influence of employee work motivation on employee performance, and (4) the influence of the use of information technology on employee performance is not mediated by the work motivation of employees of the Surabaya City Library and Archives Service.